Edipo Insepulto. La vigencia de un concepto. - Rotemberg, Horacio (Psicoanálisis: Revista de la Asociación Psicoanalítica de Buenos Aires, 2024)
The article focuses on the relevance of the Oedipus Complex in psychoanalytic theory, highlighting its function as an attractor that organizes the dynamics of the unconscious. It explores the contributions of Freud, Melanie Klein, Jacques Lacan, and Wilfred Bion, who expand the understanding of Oedipus, including the notion of an early Oedipus and its impact on the psychic structure of the subject. The text argues that the Oedipus Complex remains relevant in clinical practice, as it allows for the interpretation of the emotional and relational complexities that arise in the analytical context.